Accounting System Design At Toko Melisa - Ameilia Cantikasari; Kennardi Tanujaya (Universitas Internasional Batam, 2023)
One of the MSMEs in Batam named Toko Melisa has problems in recording its business activities. Toko Melisa still uses the cash basis method of recording and only records sales in a book. Therefore, the purpose of this community service is to help Toko Melisa make good bookkeeping by designing an accounting system from Microsoft Access. The data collection methods used for this activity are interview and observation methods. The result of this community service is the Microsoft Access accounting system, which will hopefully make it easier for Toko Melisa to build financial records, and the system can also generate financial reports automatically. The recommendations for further community service activities are to provide new solutions and innovations to accounting problems faced by other MSMEs, such as creating a system that can support tax calculations.